COMPLEX MAXILLARY AND MANDIBULAR ORAL REHABILITATION USING THE ALL-ON-6 CONCEPT, CASE REPORT - Doriana Agop Forna; Budacu Cristian Constantin; Mădălina Mihali; Carmen Tiutiucă; Kamel Earar (Romanian Society of Oral Rehabilitation, 2023)
In modern dentistry, restoring the functionality and aesthetics of edited jaws presents a continuous challenge. An increasingly popular therapeutic option for such cases is the All-on-6 concept, which involves the use of 6 dental implants to support a fixed prosthesis in the upper or lower jaw. However, there are also patients who cannot benefit from fixed protection for various reasons, such as excessive bone resorption or financial insufficiency. This article presents the innovative concept of using the All-on-6 concept with a mobilizable prosthesis, which offers significant benefits for patients. The mobilizable prosthesis is based on the same foundation as 6 dental implants but allows the patient to protect himself for oral hygiene and proper cleaning. This approach combines the advantages of fixed prosthesis and mobilizable prosthesis, offering patients good comfort and aesthetics.